Prodromos, The lecherous old woman (H 140). A Byzantine versified satyr (Circe de clásicos y modernos, 2023)
As part of the translation and study of Theodore Prodromos' texts (xiith c.) with satirical content, it is presented here the case of Κατὰ φιλοπόρνου γραός (140 Hörandner), of which we do not know a Spanish translation. The analysis of the work, in the context of its time and that one of the tradition, reveals that it is not a lyric-satirical poem but a versified satura.
Keywords: Byzantium; Theodore Prodromos; Satire; Old age